1985
DOI: 10.3109/08860228509088217
|View full text |Cite
|
Sign up to set email alerts
|

Investigations for Vesicoureteric Reflux in Children: Ultrasound vs. Radionuclide Voiding Cystography

Abstract: In this study, 53 children suffering from recurrent urinary tract infections were investigated both by ultrasound and direct radionuclide voiding cystography (RNVC). The findings were: Most high-grade vesicopelvic refluxes were detected by both methods consistently. Discrepant results of high-grade vesicopelvic refluxes were seen in 6 kidneys from 4 children. Main advantages of RNVC are the quick results and the ease of interpretation of these results. In RNVC the whole urinary tract can be observed during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The ballooning of the renal pelvis during the filling of the bladder represented the criterion for diagnosis of VUR. Only Martin et al [26] included the detection of a dilating terminal ureter as an additional criterion. A major drawback, and one that has not been adequately addressed in these studies, is the lack of a cut-off value with regards to the renal pelvic dilatation.…”
Section: Liquid or Gaseous Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ballooning of the renal pelvis during the filling of the bladder represented the criterion for diagnosis of VUR. Only Martin et al [26] included the detection of a dilating terminal ureter as an additional criterion. A major drawback, and one that has not been adequately addressed in these studies, is the lack of a cut-off value with regards to the renal pelvic dilatation.…”
Section: Liquid or Gaseous Substancesmentioning
confidence: 99%
“…The first and, in the past, most frequently administered fluid was plain physiological saline solution [24,25,26,27,28]. The ballooning of the renal pelvis during the filling of the bladder represented the criterion for diagnosis of VUR.…”
Section: Liquid or Gaseous Substancesmentioning
confidence: 99%
“…In the past two decades, various authors (3)(4)(5) have suggested ultrasonography (US) as an effective diagnostic procedure for identifying VUR; the use of microbubbles has improved this technique, yielding high sensitivity for grades III-IV VUR. More recent studies (6, 7) confirm the excellent results in the diagnosis of severe grade reflux, but point to an insufficient sensitivity of grade I VUR.…”
mentioning
confidence: 99%
“…Despite an elevated sensitivity for highgrade refluxes, the limited stability of the microbubbles conditioned the sonographic examination time and thus detection of low-grade or intermittent refluxes [24][25][26][27].…”
Section: Diagnostica Per Immaginimentioning
confidence: 99%
“…Nonostante un'elevata sensibilità per reflussi di grado elevato, la limitata stabilità delle microbolle, condizionava il tempo di osservazione ecografica e quindi l'evidenziazione di reflussi di grado minore o intermittenti [24][25][26][27].…”
Section: Urosonographyunclassified